HUBUNGAN DUKUNGAN KELUARGA TERHADAP MEKANISME KOPING PASIEN POST OPERASI MASTEKTOMI - LENNY DYANNA DEBORA HUTAPEA; Yulia Irvani Dewi; Herlina lina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The aim of this research is to determine the relationship between family support and coping mechanism to post operation mastectomy patients at Anyelir and Cendrawasih I RSUD Arifin Achmad Pekanbaru. This research use correlation descriptive design with cross sectional approximation research method. Sample of this research are 30 respondents by accidental sampling technique. Measuring tools in this research are questionnaire. Data analysis is done by univariate and bivariate analyze with Chi-Square test. Result of research show that there is relationship between family support and coping mechanism to post operation mastectomy patients with p value 0,030 (p value < 0,05). This result likely could be good contribute to medical personnel in leading because, there was a significant family support to post operation mastectomy patients. Keywords: Family support, coping mechanism, post operation mastectomy Bibliography: 54 (2000-2014)